Industrial heritage, a new tool for Olympic promotion? A comparative analysis. - Helena Roux (Via@)
Faced with the controversies surrounding the Olympic Games (OG), they are moving towards a greater integration of local challenges – economic, social and environmental. Associating the hosting of such event with the urban regeneration policies appears to be a way to include them in longer planning periods, as well as ensure they are remembered. Presented as engines of transformations, they contribute to promotion of requalified and re-invested spaces that correspond better with the image of a competitive global city. The development of tourism strategies stems from this land promotion and appears as one of the economic outlets of the post-industrial transition. On the other hand, the reuse of industrial buildings helps build a positive image and a lasting legacy for the OG, as catalysts for regeneration of brownfields in crisis – as can be seen in the official Olympic narrative. Through the analysis of three case studies, this article aims to identify how does tourism development fit into these strategies that link industrial and Olympic heritage.